2022
DOI: 10.1002/suco.202200015
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanical behavior of L‐shaped concrete‐filled steel tubular columns under axial compression

Abstract: In this paper, a total of six different ribbed and two nonribbed L-shaped concrete-filled steel tubular (CFST) short columns are designed; finite element modeling and calculations are carried out and verified with measured results. The optimal ribbing method among the ribbing methods applied is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the fly ash itself contains silicate components that can also react with alkaline substances. As a result, the alkaline substances content inside concrete is reduced again because of reaction consumption, which further accelerates the carbonation process of concrete, and the carbonation resistance performance of concrete is therefore weakened 29,42 . Felix et al 8 found that concrete carbonation depth increased with water‐binder ratio, fly ash content, and CO 2 concentration, and there was a positive statistical correlation among these parameters.…”
Section: Influence Factors Of Carbonation Depthmentioning
confidence: 99%
“…Furthermore, the fly ash itself contains silicate components that can also react with alkaline substances. As a result, the alkaline substances content inside concrete is reduced again because of reaction consumption, which further accelerates the carbonation process of concrete, and the carbonation resistance performance of concrete is therefore weakened 29,42 . Felix et al 8 found that concrete carbonation depth increased with water‐binder ratio, fly ash content, and CO 2 concentration, and there was a positive statistical correlation among these parameters.…”
Section: Influence Factors Of Carbonation Depthmentioning
confidence: 99%
“…Tu et al [28,29] analyzed the influence of parameters such as concrete and steel strength on L-shaped CFST columns through FEA and proposed a formula for calculating the axial compressive bearing capacity. Huang [30] proposed a design formula for the bearing capacity of ribbed L-shaped CFST columns that took into account improvements in concrete performance. Chen [31] proposed a simplified strength model of ECB for L-shaped CFST based on the composite yielding method.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the stiffeners could decelerate the development of local buckling, and the mechanical behavior of the welded steel tube concrete columns was better than that of ordinary steel tube concrete columns. Eight L‐shaped concrete‐filled steel tubular short columns with and without stiffeners were conducted by Huang 9 . The mechanisms of the longitudinal stress of the concrete, longitudinal stress of the outer steel tube, et al were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, under longitudinal and radial stress, the walls of SCFST are susceptible to local buckling, thus weakening the confinement effect of the steel tube on core concrete, which leads to a reduction in the bearing capacity, especially when the wall widthto-thickness ratio (B/t) is comparatively high. 1,2 In response to this problem, researchers [3][4][5][6][7][8][9][10][11] found that setting longitudinal stiffeners in the tube wall can effectively restrict the local buckling and increase the bearing capacity and ductility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation